ConVRgence (VRIC) Virtual Reality International Conference Proceedings - Richir, Simon (International Journal of Virtual Reality, 2019)
Find the articles presented at the 3 days scientific conference ConVRgence (VRIC) which take place during Laval Virtual 2019 (April 20-22).